Pelatihan dan Penilaian Aplikasi Trello Untuk Bimbingan Skripsi Online di Masa Pandemi Covid-19 - Ari Christianti (Ilin Institute, 2021)
Abstrak. The Covid-19 pandemic influences distance learning and requires lecturers to use learning technology, including undergraduate thesis guidance. The Trello is a free application that can be used for online undergraduate thesis guidance. This application is also applied to the Duta Wacana Christian University in the Management department by providing training and mentoring to undergraduate thesis supervisors. Based on the survey, lecturers were satisfied and interested in using this application for a mentoring undergraduate thesis. Furthermore, the Trello manual module was made to explain the technical instructions for the supervisor's undergraduate thesis. After approximately 3 months after training, a survey was conducted to students about Trello's evaluation. The overall results show that students are satisfied with this application and agree to use the Trello application for undergraduate thesis guidance when the Covid-19 pandemic ends. However, using the application must still require supported learning technology such as zoom or google meet. If the Covid-19 virus period ends, undergraduate thesis guidance with Trello can be done blended.